Analog Parallel Processing of Molecular Sensory Information. - de Silva, A. Prasanna; de Silva, S. Sisira K.; Goonesekera, Nalin C. W.; Gunaratne, H. Q. Nimal; Lynch, P. L. Mark; Nesbitt, Kemuel R.; Patuwathavithana, Suram T.; Ramyalal, N. L. D. Sydney (Journal of the American Chemical Society, 2007)
The article provides information about the analog parallel process of molecular sensory information. The molecular process of digital information is considered important in diverse logic operations. It involves an approach involving fluorescent photoinduced electron transfer sensors. Moreover, molecular devices lie at the smaller size-range of nanoscience and nanotechnology.